2016
DOI: 10.1161/jaha.115.002343
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antihypertensive Medication in Treatment‐Resistant Hypertension Undergoing Renal Denervation

Abstract: BackgroundAdherence to medication has been repeatedly proposed to represent a major cause of treatment‐resistant hypertension (TRH); however, treatment decisions such as treating TRH with renal denervation depend on accurate judgment of adherence. We carefully analyzed adherence rates to medication before and after renal denervation and its effect on blood pressure (BP) control.Methods and ResultsEighty patients with TRH were included in 2 prospective observational studies that assessed the difference of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 35 publications
4
36
1
2
Order By: Relevance
“…8,23,27 In these studies, an increase or decrease in the rate of adherence to the treatment with age may be due to the presence of comorbid chronic diseases, perceived health status, or differences in giving or receiving health care. 7,24 While gender is not a determinant for the rate of adherence to the pharmacological treatment in some studies the adherence rate is high in women in other studies. 8,19 In the present study, although not significant, the rate of adherence was high in women as in the literature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…8,23,27 In these studies, an increase or decrease in the rate of adherence to the treatment with age may be due to the presence of comorbid chronic diseases, perceived health status, or differences in giving or receiving health care. 7,24 While gender is not a determinant for the rate of adherence to the pharmacological treatment in some studies the adherence rate is high in women in other studies. 8,19 In the present study, although not significant, the rate of adherence was high in women as in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…Rates of adherence to pharmacological treatment range between 52% and 87% in studies conducted in Turkey and between 48% and 84% in studies conducted abroad. 7,8,12,15,[19][20][21][22][23][24] The WHO has reported that rates of adherence to pharmacological treatment by hypertension patients vary between 20% and 80%. 25 Thus, it can be concluded that the rate of adherence to pharmacological treatment in this present study conducted in a semi-urban region in Turkey overlaps with the rates reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The adherence to antihypertensive therapy was not specifically investigated in this study. However, two recently published studies indicate that patients decrease their adherence to antihypertensive therapy following renal denervation, with more pronounced reductions observed in patients not responding to treatment in terms of office blood pressure changes [21,22]. All RDN procedures were performed with the first generation Symplicity Flex catheter (Medtronic, MA, U.S.A.).…”
Section: Discussionmentioning
confidence: 99%
“…33 It should be noted, however, that several studies have recently shown that nonadherence to treatment is not affected by RDN, nor did it influence RDN results. [34][35][36][37] Moreover, this limitation is compensated for by strict inclusion criteria and by the fact that all patients maintained their baseline antihypertensive drug regimen for the 3-month follow-up.…”
Section: 18mentioning
confidence: 99%